Optimizing Bacillus pasteurii spore germination and unveiling impermeability mechanisms in microbial self-healing concrete - Hu, Yingying; Liu, Weitao; Zhang, Yutao; Hu, Xuelong (Frontiers in Microbiology, 2025)
This study investigated the impact of key factors on spore germination of Bacillus pasteurii, a self-healing bacterium for concrete, and elucidated its impermeability mechanism to provide theoretical and practical guidance for advanced self-healing concrete development. Controlled experiments determined optimal germination conditions: 2 g/L microcapsule concentration, pH 8, and 1 g/L inosine, yielding peak germination efficiency that highlights parameter synergies. Thermal stimulation for 3 minutes effectively triggered germination, presenting a practical activation approach. MIP and SEM analyses were employed to characterize concrete microstructure. Results showed the alkaline concrete matrix facilitated B. pasteurii physiology, while Ca2+ had no inhibitory effect, enabling calcium-based additives in formulations. B. pasteurii-containing mortar enhanced cement hydration stability; MIP revealed self-healing concrete had an infiltration fractal cone number of 2.832 and trunk fractal dimension of 2.306, similar to conventional materials, indicating no increased structural complexity. Environmental erosion primarily affects 300–10,000 nm pores, pinpointing durability targets. SEM and MIP analyses confirmed B. pasteurii-induced vaterite and aragonite calcium carbonate crystals integrated with tobermorite, reducing porosity and enhancing mechanical strength. These findings indicate the bacterium’s potential in self-healing systems, though future research should address complex physicochemical influences and bacterial gradient domestication to improve environmental adaptability.